Laudato si' and the Use of Scientific Research in Theology and Public Policy. - Scherz, Paul (Heythrop Journal, 2018)
The article presents the author's insights regarding Pope Francis' encyclical "Laudato si'" and the use of scientific research in public policy and theology. Topics include the engagement of Catholic Magisterial documents with scientific research, discussion of genetically modified (GM) organisms in the encyclical, and views of Pope Francis on the benefits and harms of reliance on scientific research.